THE SUCCESS RATE OF THE MANDATORY PREGNANT COW PROGRAM (SIWAB) PROGRAM IN AN EFFORT TO INCREASE THE BIRTH RATE OF BALINESE CATTLE IN THE DISTRICT OF KARANGASEM - N., Filbert,; Sumardani, N. L. G.; Ardika, I N. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This study aims to see the success rate of the Compulsory Pregnant Cow (SIWAB) program in Karangasem Regency. This research was conducted using the purposive sampling method and interviews with farmers. Primary data was obtained from respondents about reproductive understanding and secondary data was obtained from recording inseminators in 2018-2019 at the Karangasem Regency Livestock, Marine and Fisheries Office. The research variables were measured, namely Service Per Conception (S/C), Conception Rate (CR), Calving Rate (CvR), farmers' knowledge about reproductive understanding in supporting the SIWAB program. The data is presented descriptively by displaying the percentage of variables measured. To read the value of the success rate of the SIWAB program, it is compared with the success score of the program. The results of the study show that the S/C figure in 2018 is 1.66 and in 2019 is 1.38 with an optimal success rate. The percentage of CR in 2018 was 65.12% and in 2019 was 77.57% with an optimal success rate. The percentage of Calving Rate in 2018 was 55.67% and in 2019 was 52.97% with an optimal success rate. Based on the results of the study, it can be concluded that the SIWAB program in Karangasem Regency has been implemented optimally based on the data of the recording inseminator figures. The success of the SIWAB program is fundamentally supported by the level of understanding of breeders about reproduction, sexual detection, inseminator skills, IB timeliness, Balinese cattle performance, livestock health and the quality of frozen semen used.